Regional Socio-economic System of Krasnodar Territory: The Current State and Development Trends - Pechenaya, Ludmila T.; Domarev, Ivan E.; Avanesova, Alexandra E.; Durdyeva, Jennet A.; Aslanov, Dmitriy I. (International Journal of Economics and Financial Issues, 2016)
Control Strategy of socio-economic development of Krasnodar region - a system of government measures, based on the long-term priorities of the regional socio-economic policies that are in indissoluble unity, and the relationship with the national strategic priorities. However, in the Krasnodar region retained extensive, inefficient management and use of resources. In general, the existing methods and developed the governance structure of socio-economic development of Krasnodar region in many respects do not meet the changed conditions of its functioning, that it becomes an obstacle to its further successful development of more. Currently existing strategy of socio-economic development of Krasnodar region made its developers in the logic of the traditional strategic and scenario planning is not. Strategic management of socio-economic development of Krasnodar region must take into account the assessment of the degree of satisfaction of the population’s needs in material goods and a variety of services compared with rational norms of consumption. Given prevailing in the society differentiation of living standards need to prioritize strategic management. Defining features of strategic management of development of the Krasnodar Territory is based on a study of it as a system and organization. Keywords: region, socio-economic systems, development trends, strategic priorities JEL Classifications: G11, I28, R38